The effectiveness of chiropractic vertebral manipulation for the treatment of migraine: a systematic review - Silva, Amanda Karolina Lopes (2022)
The present study, registered with PROSPERO under the number CRD42022321874. Aims: Discuss current randomized clinical trials in the literature to investigate the effectiveness of chiropractic spinal manipulation in the treatment of migraine. Methodology: The search was carried out during the period from February to May 2022 through the databases: PubMed, Scielo, PEDro and VHL, limited to articles identified as randomized clinical trials (RCTs), in any language, which used as primary intervention chiropractic spinal manipulation and migraine as a primary disorder investigated. The search terms included: Headache, migraine, manipulation, chiropractic. Results: Our search identified 4 RCTs that met all inclusion criteria. The methodological quality was mostly low and ranged between 4 and 8 on the PEDro scale. Interventions lasted from 2 to 6 months and outcome averages included migraine days, pain, migraine intensity and disability. 3 RCTs showed improvements compared to the control group in migraine days, intensity, duration and disability. 1 RCT did not obtain relevant results in combining spinal manipulation with the use of amitriptyline. Conclusion: However, it was not clear from the results whether chiropractic spinal manipulation can be effective in the treatment of migraine, so it suggests that other much better elaborated studies be added in the literature, before stating whether this treatment can be effective or not for pain.